Pengaruh Profitabilitas, Ukuran Perusahaan, Struktur Aktiva, Dan Likuiditas Terhadap Struktur Modal Pada Perusahaan Makanan Dan Minuman Periode 2018-2020 - Ragil Fananda Sofyan; Budi Wahono; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstrak Financial decisions related to capital or funds in the company. Capital is business capital that is the basis for running a business. Decisions that are closely related to the selection of financing sources that come from and can affect the value of the company. This study aims to examine and analyze the effect of profitability, firm size, asset structure, and liquidity on capital structure. The object of this research is food and beverage companies listed on the Indonesia Stock Exchange during the period 2018-2020. This type of research is causative. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 period as many as 26 companies and a sample of 14 companies. The sampling method is purposive sampling, so the number of units of analysis is 42 observations. The method of data analysis is through multiple linear regression analysis. The results showed that profitability, firm size, asset structure, and liquidity simultaneously had a significant effect on capital structure. Partially, liquidity has a significant effect on capital structure, while profitability, firm size and liquidity have no significant effect on capital structure. Keyword : Profitability, Size COmpany, Asset Structure, Liquidity, Capital Structure